Effect of internal barriers on innovation performance in embryonic SMEs in Malaysia - Hasliza Abdul Halim; Tarnima Warda Andalib; Noor Hazlina Ahmad; T. Ramayah (Asian Academy of Management Journal, 2023)
Manufacturing small and medium enterprises (SMEs) need to propel their creativity and innovativeness to enhance their innovation performance in the competitive and fast-changing environment. The current environment has transformed the internal working pattern, structure, and communication system to survive the rough business ecosphere. Consequently, SMEs encountered innumerable barriers to achieve the innovation performance and the SMEs should recognise the internal barriers so that they are able to accelerate their innovation performance. Therefore, this study aims at examining the internal barriers namely constraint in financial resources, constraint in technology, and constraint in human resources that hamper the innovation performance among the Malaysian manufacturing SMEs. This study embarked on two phases of data collection. First phase includes a series of semi-structured interviews with 15 participants from 5 SMEs via snowballing technique to gather their insights on internal barriers that impede innovation performance. For second phase, the survey method was adopted, and 217 SMEs responded to the survey. All the responses were analysed using SmartPLS technique. The interview findings demonstrate that all the internal constraints are indeed important for SMEs to grasp and serve as the obstacles for innovation performance. Nevertheless, from the quantitative analysis, only financial constraints serve as the significant barrier that impede innovation performance. To summarise, this research produces insights on decisive proof regarding internal barriers that inhibit the manufacturing SMEs to achieve innovation performance.